A atenção seletiva como constructo neurocognitivo potencial para a aprendizagem da noção de funções orgânicas oxigenadas - Santos, Eliel Cardoso dos (2024)
In the process of learning Organic Oxygenated Functions (FOO), selective attention is fundamental, as it allows the student to focus on relevant information about functional groups, properties and reactions, filtering out irrelevant or distracting stimuli. This optimizes the acquisition and retention of new knowledge, directing cognitive resources to what really matters, such as understanding molecular structures and their chemical transformations in the learning context. In view of this, the general objective of this research was to analyze a Didactic Sequence (DS) considering the neuronal functioning of selective attention during the process of learning the notion of Oxygenated Organic Functions, recommended for students in the 3rd year of High School in a public school in the city of Aporá. To this end, the investigation was conducted in an exploratory and experimental manner, due to the need for studies and application in this area, supported by the methodological principles of Classical Didactic Engineering, established by Michèle Artigue. A historical-epistemological analysis was carried out on Organic Functions with the aim of identifying epistemological obstacles, according to Bachelard, and didactic obstacles, according to Brousseau, in addition to analyzing approaches to the organization and habitual teaching of this knowledge in official documents and in chapters of four textbooks. These analyzes resulted in the conception of DS based on selective attention and brain processing of information, theoretically supported by Neuroscience and Cognitive Neuroscience, with authors such as Gazzaniga et al. (2018, 2019), Kandel (2014), Lent (2010), Sternberg (2010), and Cosenza and Guerra (2011), as well as the Feature Integration Theory, developed by Treisman and Gelade, which explains search mechanisms of stimuli based on characteristics of the FOO presentation. The DS was created by the researcher and is composed of ten activities based on the principles of Brousseau's Theory of Didactic Situations, with the purpose of modeling the learning process, using generic didactic resources to develop attentional focus. The activities were organized and applied in four moments, in which tests, protocols and photographic and audiovisual records were used to collect data. These were systematized using descriptive statistics, analyzed and compared between a priori and a posteriori analysis. Thus, most of the hypotheses for each of the activities were confirmed, as well as the objectives were achieved, validating the DS. The results indicate that the generic teaching resources incorporated in the activities played a fundamental role in improving the students' state of selective attention in the process of learning the notion of FOO. This reveals the activation of specific regions of the cerebral cortex, such as the occipital and parietal, during the execution of activities, demonstrating the positive impact of visual stimuli on student participation and engagement. Therefore, this research contributes to EM chemistry teachers by presenting a DS on learning the notion of FOO, based on Cognitive Neuroscience and using generic teaching resources to develop students' selective attention in this process.